Phlebotominae (Diptera: Psychodidae) of human leishmaniosis sites in Tunisia - Ghrab J.; Rhim A.; Bach-Hamba D.; Chahed M.K.; Aoun K.; Nouira S.; Bouratbine A. (Parasite, 2006)
In order to identify the phlebotomine sandfly populations in Tunisian leishmaniosis foci, an entomological survey was carried out through three entomological seasons (2002-2003-2004) in 19 visceral and cutaneous leishmaniosis areas, located in six bioclimatic zones. Sandfly collections were based on light and sticky traps placed around human leishmaniosis cases. 8,722 phlebotomine sandflies belonging to 12 species were collected. The dominance of subgenus Larroussius species in northern foci, Phlebotomus papatasi in south-western foci and their co-dominance in the centre of the country is in accordance with the distribution of Leishmania infantum and L. major in Tunisia. The low density found in the historical zoonotic cutaneous leishmaniosis focus of Metlaoui in the south-west may indicate the high competence of the local populations. Studied phlebotomine settlements have showed a low specific diversity in most of the studied sites. In L. infantum areas, the dominant species were respectively: P. perfiliewi in the cutaneous leishmaniosis site of the humid bioclimatic stage, P. perniciosus in the cutaneous and visceral leishmaniosis foci of semi-arid and arid bioclimatic stages and P. longicuspis in the visceral leishmaniosis focus of saharan bioclimate. In the zoonotic cutaneous leishmaniosis foci, P. papatasi was a dominant species. In the well-known southeastern foci of cutaneous leishmaniosis due to L. killicki, P. sergenti was a dominant species with P. perniciosus. In the central emerging foci of L. killicki, P. perniciosus was a dominant species in some sites whereas it was very rare in others. In these sites, the subgenus Paraphlebotomus was always present with a higher abundance of P. alexandri than P. sergenti.